Context related rich information delivery to mobile users using smart posters - Ayu, Media Anugerah (s.n, 2012)
This project explores the use of NFC-enabled mobile phones to interact with NFC-tagged Smart Posters, in order to deliver rich information to the users in a pleasant, convenient, and easy way. This initial work on NFC-tagged Smart Poster will be a significant contribution to our bigger research study on context aware computing, especially on delivering context aware rich information to mobile users